Evaluation of ISSR Primer Applicability for Interspecific Differentiation of Marchantia from West Java - Susilo Susilo; Maryanti Setyaningsih; Suci Lestari; Jahanzaib Ali (Jurnal Biodjati, 2026)
Liverworts of the genus Marchantia play important ecological roles in humid tropical ecosystems; however, molecular marker evaluation for tropical taxa remains limited. This study aimed to assess the amplification performance and cross-species applicability of selected Inter Simple Sequence Repeat (ISSR) primers for interspecific molecular differentiation of Marchantia species from West Java, Indonesia. Four species (M. emarginata, M. geminata, M. paleacea, and M. polymorpha) were analyzed using five ISSR primers. Genomic DNA was extracted using a modified CTAB protocol and amplified through single-primer ISSR-PCR assays. Amplification profiles were scored as the presence or absence of dominant bands. Three primers (F218, F231, and F209) generated clear and reproducible multi-locus banding patterns, producing a total of 21 scorable fragments, whereas BS537 and BS3 failed to amplify detectable products. Polymorphism Information Content (PIC), interpreted as an index of band discrimination capacity across species, ranged from 0.70 to 0.91, with F209 and F218 showing the highest informativeness. The results demonstrate that the selected ISSR primers enable reliable interspecific discrimination among the taxa examined and provide a practical framework for preliminary molecular screening of tropical bryophytes. These findings support the use of validated ISSR primers in future taxonomic and comparative genetic studies of non-model liverwort species.